2019
DOI: 10.1016/j.breast.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported health problems and healthcare use after treatment for early-stage breast cancer

Abstract: Background: A clear picture of treatment-related health problems following breast cancer treatment is useful in anticipating the informational and other needs of patients during follow-up. This study aimed to identify treatment-related health problems in breast cancer patients up to five years after diagnosis. Secondly, the use of care associated with these health problems was identified. Methods: 876 surgically-treated female patients diagnosed between 2012 and 2016 with early-stage breast cancer were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…These findings reflect that survivors are still suffering from their diagnosis of advanced melanoma and the treatment trajectory. Previously, physical, psychosocial, and cognitive problems have been reported and associated with reduced HRQoL levels in cancer survivor populations [32][33][34]. In this study, 61% received systemic non-ICI treatment and almost all survivors had surgery prior to ipilimumab.…”
Section: Discussionmentioning
confidence: 74%
“…These findings reflect that survivors are still suffering from their diagnosis of advanced melanoma and the treatment trajectory. Previously, physical, psychosocial, and cognitive problems have been reported and associated with reduced HRQoL levels in cancer survivor populations [32][33][34]. In this study, 61% received systemic non-ICI treatment and almost all survivors had surgery prior to ipilimumab.…”
Section: Discussionmentioning
confidence: 74%
“…Patient-Reported Outcome Measures (PROMs) are suggested as symptom detection method [21, 23], but implementation in daily practice is hampered [21, 24, 25]. Furthermore, support in coping with symptoms may be insufficient, as patient-reported health symptoms consistently over time (years) after diagnosis [9, 11, 26, 27]. Wu et al describe that 92% of patient-reported residual symptoms 1 year after diagnosis, and 61% reporting pain, fatigue, and sleep disturbance up to 5 years after diagnosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Even though treatment protocols are currently less aggressive, it was found in literature that declines after breast cancer diagnosis can be associated with chemotherapy and surgery treatments 7 . It is important to highlight that most patients in the present study were undergoing chemo- therapy treatment, and had undergone mastectomy for breast cancer, which can worsen the fatigue perception in more severe degrees 5 . This study showed that women undergoing physiotherapy reported significantly higher levels of fatigue when compared to those who were not and were more likely of having mild to severe fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…When submitted to treatment, women may suffer physical, psychological, emotional or social consequences 5 . Fatigue, defined as an unpleasant physical sensation, with symptoms of extreme tiredness and exhaustion, is considered one of the most prevalent consequences in cancer patients, severely impacting quality of life, decreasing daily functional capacity 6 .…”
Section: Introductionmentioning
confidence: 99%